Phytosanitary state of open-field vegetable crop agroecosystems of the genus Solanum, Raphanus, Brassica in the central part of the Right-Bank Forest-Steppe of Ukraine - S. Shchetina; I. Mostoviak; V. Fedorenko (Карантин і захист рослин)
Goal. Phytosanitary assessment and determination of pest and disease prevalence and development in open-field vegetable crop plantings of the genus Solanum (tomato, pepper, eggplant), genus Raphanus (radish, oilseed radish, common radish, black radish, daikon), and genus Brassica (cabbage, cauliflower, broccoli) in the Central Part of the Right-Bank Forest-Steppe Region of Ukraine.